KAIDAH FIQHIYAH FURU’IYAH: PENERAPANNYA PADA ISU KONTEMPORER - Thalhah Thalhah (IAIN Ambon, 2017)
The Fiqhiyyah rules cannot be denied as a result of the creation of Islamic scholar thinking with guidance of nash on viewing and examining a number of Islamic jurisprudence issues as well as to be one solution to the legal problems that developed over time. The Islamic jurists have agreed on the existence of rules are categorized as principal rules or basic rules which essentially can be the parent of a number of rules are categorized as branch rules (furu'iyah). Some of this branch rules can be used simultaneously to solve some cases and events related to the current economic field. The problem of current account, savings, deposits, set its law by using most common furuiyah rules with the additional rules relating to the necessity to eliminate the harm. While the financing of Letters of Credit (L/C) is defined by the Sharia National Council using five rules. Sale and purchase of Istishna parallel with eight fiqhiyyah rules. While the Sharia Current Account financing by the Sharia National Council is considered sufficiently using four rules in deciding it’s law. Key words: Fiqh furu'iyah rule, contemporary economic issues